2000
DOI: 10.1021/ja000519v
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Pyrimidine-Selective DNA Binding:  Analysis of Calicheamicin Oligosaccharide Derivatives by Capillary Electrophoresis

Abstract: Synthetic derivatives of the calicheamicin oligosaccharide were designed to probe the molecular basis for pyrimidine recognition. Binding affinities of the oligosaccharide derivatives for a range of DNA sequences were determined using capillary electrophoresis. The results show that having an iodo-substituted C-ring is neither necessary nor sufficient for pyrimidine-selective binding. Pyrimidine-selective binding depends on maintaining the overall shape and rigidity of the calicheamicin oligosaccharide. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
17
1
1
Order By: Relevance
“…K was 4 21 calculated to be (4.7560.30)?10 M . The results of K in CZE and ACE were a little smaller than the value obtained by Biswas et al using CZE [19]. The buffer used in our work and theirs.…”
Section: 3contrasting
confidence: 80%
See 2 more Smart Citations
“…K was 4 21 calculated to be (4.7560.30)?10 M . The results of K in CZE and ACE were a little smaller than the value obtained by Biswas et al using CZE [19]. The buffer used in our work and theirs.…”
Section: 3contrasting
confidence: 80%
“…concerning the research of DNA-drug interactions Capillary electrophoresis (CE) has become a and even quantitative determination of the binding robust separation technique in the past few years constants using CE [17][18][19][20]. Small duplex oligoowing to its several advantages such as short analysis nucleotides can be used as appropriate molecules for time, low sample size requirement, high efficiency the investigation of binding properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their initial modeling study, Hawley et al had first suggested a prominent role for the aromatic iodine for DNA binding. 42 These studies revealed that in the iodo-containing aryl rhamnoside part of the oligosaccharide, the ring C iodo-guanine amino interaction is worth $ 0.6 kcal/mol. Li et al using gel cleavage kinetics with calicheamicin observed decreased binding affinity in sequences containing an exocylic guanine amino group on the targeted nucleotide on the AGGA side of the TCCT/AGGA tracts when the iodine was replaced in the order of bromine, chlorine, fluorine, methyl, and hydrogen.…”
Section: Structural Features Of the Oligosaccharide Responsible For Tmentioning
confidence: 99%
“…CZE was used to evaluate the interactions between calicheamicin and oligonucleotides containing different sequences. It is the first CE study reporting a binder that utilizes a carbohydrate moiety to recognize DNA and a minor groove binder that is selective for pyrimidine sequences such as TCCT, though most of DNA minor groove binders prefer AT-rich regions of DNA [113]. When actinomycin D (Act D) served as ligand in the running buffer, a self-complementary oligomer d(CGTGCACG) showed a migration acceleration due to Act D binding.…”
Section: Dna-small Molecule Interactionmentioning
confidence: 99%